Pendidikan Sebagai Alat Transformasi Sosial Perspektif Filsafat Ilmu - Umar Faruq; M. Yunus Abu Bakar (Concept: Journal of Social Humanities and Education, 2025)
Education plays a strategic role as a tool for social transformation capable of shaping individual character, addressing social inequality, and driving societal change. In the Indonesian context, character education has become a central issue in building a generation that is faithful, pious, morally upright, and responsible in accordance with the values of Pancasila. Through a holistic approach, character education integrates spiritual, intellectual, emotional, and social aspects to create quality individuals. Furthermore, learning methods that involve role modeling, habituation, and community participation emphasize the importance of collaboration between schools, families, and communities. As an agent of change, education also aims to create a knowledge-based society where science, innovation, and problem-solving serve as key pillars. Through lifelong learning, problem-based learning, and collaborative approaches, education provides space for the development of human potential relevant to global challenges. However, challenges such as educational disparities, curriculum relevance, and teacher capacity remain obstacles that need to be addressed through inclusive policies, continuous training, and improvements in educational infrastructure. By adopting an integrated approach, education can serve as a solid foundation for building a just, inclusive, and adaptive society in response to social changes.